The association between omega-3 fatty acid biomarkers and inflammatory arthritis in an anti-citrullinated protein antibody positive population - Gan, Ryan W. (Rheumatology (Oxford), 2017)
OBJECTIVES: Higher circulating omega-3 fatty acids (n-3 FAs) are associated with a lower prevalence of anti-CCP antibodies and RF in subjects without RA. We examined whether, in anti-CCP(+) subjects, n-3 FAs also play a role in development of inflammatory arthritis (IA). METHODS: At Colorado-based health fairs from 2008 to 2014, participants without a previous diagnosis of RA who were anti-CCP3(+) (n = 47) were recruited into a follow-up study; symptom assessments and joint examinations were conducted every 6 months for the determination of IA. We measured n-3 FAs as a percentage of total lipids in red blood cell membranes (n-3 FA%) at each visit. RESULTS: We detected IA in 10 anti-CCP3(+) subjects (21%) at the baseline visit. Increased total n-3 FA% in red blood cell membranes [odds ratio (OR) = 0.09, 95% CI: 0.01, 0.76], specifically docosapentaenoic acid (OR = 0.16, 95% CI: 0.03, 0.83) and docosahexaenoic acid (OR = 0.23, 95% CI: 0.06, 0.86), was associated with a lower odds of IA at the baseline visit, adjusting for n-3 FA supplement use, current smoking, RF(+), elevated CRP(+) and shared epitope. We followed 35 of the anti-CCP3(+) subjects who were IA negative at baseline and detected 14 incident IA cases over an average of 2.56 years of follow-up. In a time-varying survival analysis, increasing docosapentaenoic acid significantly decreased risk of incident IA (hazard ratio = 0.52, 95% CI: 0.27, 0.98), adjusting for age at baseline, n-3 FA supplement use, RF(+), CRP(+) and shared epitope. CONCLUSION: n-3 FAs may potentially lower the risk of transition from anti-CCP positivity to IA, an observation that warrants further investigation.